PEMBINAAN MENTAL MELALUI TERAPI ISLAM - Alang, HM Sattu (Jurusan Bimbingan dan Penyuluhan Islam, 2021)
Islam is a religion of therapy. In mental development, there are several Islamic instructions among them; Strengthen the spirituality of the individual by instilling faith in God and forgiveness in Him and not to obey Him. Mastering the physical needs side of the individual by controlling all the motivations and emotions associated with it. It also defeats excessive desire and lust and learns important ways and habits that realize mental health. By having a healthy soul, the individual has matured, both emotionally and socially to be able to form a good personality that is always desired by every human being. In the mental development of a person there are several concepts of Islamic therapy that must be given. Free association therapy, giving full attention and following the rules of absistence. Furthermore, the method of therapy according to Islam is seen from the way of taking, the methodology of Islamic psychotherapy is based on four ways, namely with the Istimbath method, which is derived directly from the Quran, iqtibas method, Istiqra'iy method, and combining the method of comprehensive Jami' bayna nufus al-zakiyyah wa-al 'uqul al-shfaiyyah. Related to the process of human mental development in the world of Sufism and order is known there are three stages, namely: takhalli stage, Tahalli stage and Tajalli